Characterization of a New, Country Bean (Lablab purpureus) Lineage of Bean Common Mosaic Necrosis Virus - Rahman, Mohammad M (Plant disease, 2024)
Country bean (Lablab purpureus, family Fabaceae) is grown in subsistence agriculture in Bangladesh as a multipurpose crop for food, animal feed, and green manure. This study was undertaken to investigate the genetic diversity of bean common mosaic necrosis virus (BCMNV, genus Potyvirus, family Potyviridae) in country beans. Leaf samples from country beans showing yellowing, vein banding, and mosaic symptoms were collected during field surveys between 2015 and 2019 cropping seasons from farmers' fields in different geographic regions. These samples were tested by serological and molecular diagnostic assays for the presence of BCMNV. Virus-positive samples were subjected to high-throughput Illumina sequencing to generate near-complete genomes of BCMNV isolates. In pairwise comparisons, the polyprotein sequences of BCMNV isolates from Bangladesh showed greater than 98% identities among themselves and shared less than 84% sequence identity at the nucleotide level with virus isolates reported from other countries. In the phylogenetic analysis, BCMNV isolates from Bangladeshi country beans formed a separate clade from virus isolates reported from common beans in other countries in the Americas, Africa, Europe, and from East Timor. Grow-out studies showed seed-to-seedling transmission of BCMNV, implying a possible seedborne nature of the virus in country beans